Application Potential Of SMS DC Smelter Technology For The Pyrometallurgical Industry In South Africa - R. Degel (The Southern African Institute of Mining and Metallurgy, 2011)
Keywords: Pyrometallurgy, DC furnaces, electric smelter, FeCr, FeNi, FeMn, Si metal, ferro-alloys, platinum production, circular furnace, energy recovery system In 1906, the first submerged-arc furnace was supplied by SMS Siemag. Since then, the division has become established in various industries such as ferro-alloys and non-ferrous metals, and in numerous other special applications. During the evolution of this technology, more efficient units with longer lifetimes were developed. Today, especially the potential of DC-based smelters, raises worldwide attention, with some projects having already started to implement this kind of technology. This paper evaluates SMS Siemag?s general viewpoint regarding the potential application of DC smelter technology and possible options for the ferro-alloy and non-ferrous industry. SMS Siemag is currently executing a FeCr project in Kazakhstan, where four of the world?s largest closed-type DC smelting furnaces, with a power input of 72 MW, will be installed. These furnaces include the latest technological features of modern DC smelters, which are described in this paper. SMS Siemag has started a long-term research and development project allowing a direct comparison of AC versus DC technology on a large scale, using a recently installed 1 MVA test furnace at the IME at the University of Aachen, in Germany. For open-type ferro-alloy and Si-metal furnaces, SMS Siemag has developed an energy recovery system, which is presented in this paper.